Cutting edge : consumers' attitudes towards advertisements portraying female models who have undergone cosmetic surgery : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Tipgomut, Pornchanoke (Massey University, 2018)
Advertisers portray idealized female models who have gained attractiveness from cosmetic surgery in their advertisements without knowing the effects of this decision. This thesis aims to address this unknown point about the portrayal of idealized female images in advertisements. It is a controversial topic, but an important topic, given the prominent use of cosmetic surgery in contemporary society. Two exploratory studies and five quantitative studies were conducted in Thailand to investigate: female consumer’ reactions to models that underwent cosmetic surgery, male consumers’ reaction to such models and the influence of cosmetic surgery on Asian beauty types. The results show that cosmetic surgery only enhances perceived attractiveness when the model underwent many cosmetic surgery changes and if female consumers do not perceive these surgery changes. However, both male and female consumers can detect surgery changes when the model has undergone many changes. In sum, cosmetic surgery only affects attractiveness if many procedures have been conducted. But then the probability of detection is high, and detection overrides the positive effect of cosmetic surgery on perceived model attractiveness. This dark side does not occur amongst male participants in the reported experiments. We found that males believe in the negative news of claiming that the model has undergone cosmetic surgery, but such claims do not affect perceived model attractiveness. However, a claim of no surgery on model’s face provides benefit, as it increases perceived model attractiveness amongst male experiment participants, and consequently increases advertising effectiveness. Concerning the third topic, previous classifications of female models’ beauty types are based on a Western perspective. However, we have shown that Asian model beauty types are classified differently from Western perspectives. From an Asian perspective female model beauty types are classified into three main groups: Natural Cuteness (cute, natural, sweet, and local beauty), Non-Local/Surgery (Western look, Korean style, and surgery beauty), and Sexy Beauty (sexy, cool, and sharp beauty). Our results indicate that cosmetic surgery enhances Non-Local/Surgery beauty and Sexy beauty. However, the most effective beauty type in terms of advertising effectiveness is Natural Cuteness, which cosmetic surgery cannot enhance.
Keywords: Women in advertising; Thailand; Models (Persons); Surgery, Plastic; Social aspects; Feminine beauty (Aesthetics); Consumers; Attitudes